Traditional plant use in the National Park of Cilento and Vallo di Diano, Campania, Southern, Italy. - Di Novella, Riccardo; Di Novella, Nicola; De Martino, Laura; Mancini, Emilia; De Feo, Vincenzo (Journal of ethnopharmacology, 2012)
AIM OF STUDY: This paper reports an ethobotanical survey of the traditional uses of medicinal and useful plants in an area of the National Park of Cilento and Vallo di Diano, Campania, Southern Italy. MATERIALS AND METHODS: This study conducted between 2009 and 2011, gathered information on the medicinal plants traditionally used in Southern Italy (Campania Region). In all, we interviewed 70 key informants, whose age ranged between 50 and 85 years. This people belonged to families which had strong links with traditional activities of the area. RESULTS: The research resulted to the identification of 192 plants belonging to 64 families. Among the species reported, 86 are used in human medicine, 15 in veterinary medicine, 69 as human foods, 18 as animal feed, 61 for domestic and 8 for agricultural uses. CONCLUSION: A survey of the available literature on Southern Italy ethnobotany reveals that some species have been never reported and about 10% of cited uses are new. Data obtained show that in the studied area the folk use of plants is alive and still derives from daily practice.
The following values have no corresponding Zotero field: publisher: Elsevier accession-num: 23159473
Keywords: Agriculture; Agriculture: methods; Animal Feed; Animal Feed: utilization; Data Collection; Ethnobotany; Ethnobotany: methods; Ethnobotany: statistics & numerical data; Ethnomedicine; Food; Humans; Italy; Medicinal; Medicine; National Park of Cilento and Vallo di Diano; plant traditional uses; Plants; Traditional; Traditional: utilization; Veterinary medicine; Veterinary Medicine: methods

Folk phytotherapeutical plants from Maratea area (Basilicata, Italy). - Guarrera, Paolo Maria; Salerno, Giovanni; Caneva, Giulia (Journal of ethnopharmacology, 2005)
Field ethnobotanical survey was undertaken for the period of 2002-2003 in the Tyrrhenian part of the Basilicata region of southern Italy. Data of 56 species of plants belonging to 29 families where gathered through interviews; among the species, 47 are used in human therapy, 6 as insect repellents, 15 in veterinary medicine, 1 for its ichthyotoxic properties and 3 for magic therapeutic purposes. The most important findings in ethnomedicine relate to Nasturtium officinale (renal colic, liver diseases), Foeniculum vulgare subsp. piperitum (mouth ulcers), Leopoldia comosa (toothache, headache), Micromeria graeca subsp. graeca (coughs) and Ceterach officinarum (malaria), while in the ethnoveterinary field, we have Pteridium aquilinum (wolf bites) and Spartium junceum (fractures of animal limbs).
Keywords: Abdominal Pain; Abdominal Pain: drug therapy; Anthelmintics; Anthelmintics: therapeutic use; Antiparasitic plants; Basilicata; Common Cold; Common Cold: drug therapy; Cough; Cough: drug therapy; Diuretics; Diuretics: chemistry; Diuretics: therapeutic use; Ethnobotany; Ethnopharmacology; Ethnopharmacology: methods; Furunculosis; Furunculosis: drug therapy; Geography; Humans; Italy; Lung Diseases; Lung Diseases: drug therapy; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plant Preparations; Plant Preparations: therapeutic use; Plants; Skin Diseases; Skin Diseases: drug therapy; Time Factors; Traditional; Veterinary plants; Wound Healing; Wound Healing: drug effects; Wounds and Injuries; Wounds and Injuries: drug therapy

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suárez, M A; Pérez, A (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy

Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F. M.; Suarez, M. a; Pérez, A. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)The following values have no corresponding Zotero field: accession-num: 9032619
Keywords: Data Collection; Humans; Medicinal; Medicinal plants; Medicinal: classification; Medicine; Phytotherapy; Plants; southern Spain; Spain; Structure-Activity Relationship; Traditional; Traditional phytotherapy